ON THE BENEFITS OF PHILOSOPHY AS A WAY OF LIFE IN A GENERAL INTRODUCTORY COURSE. (27th April 2020) - Wright, Jake
Abstract: Philosophy as a way of life (PWOL) places investigations of value, meaning, and the good life at the center of philosophical investigation, especially of one's own life. This essay argues that PWOL is compatible with general introductory philosophy courses, further arguing that PWOL‐based general introductions have several philosophical and pedagogical benefits. These include the ease with which high‐impact practices, situated skill development, and students' ability to "think like a disciplinarian" may be incorporated into such courses, relative to more traditional introductory courses, as well as the demonstration of philosophy's value to students by explicitly tying philosophical investigation to students' own lives.